Nuclear Factor 1 Synergizes with Progesterone Receptor on the Mouse Mammary Tumor Virus Promoter Wrapped around a Histone H3/H4 Tetramer by Facilitating Access to the Central Hormone-responsive Elements - Vicent, Guillermo Pablo (American Society for Biochemistry and Molecular Biology, 2010)
Steroid hormones induce transcription of their responsive genes by complex mechanisms including synergism between the hormone receptors and other transcription factors. On the mouse mammary tumor virus (MMTV) promoter progesterone induction is mediated by the reciprocal synergism between progesterone receptor (PR) and the ubiquitous transcription factor nuclear factor 1 (NF1). PR binding mediates ATP-dependent displacement of histone H2A and H2B, enabling NF1 access to its target site. In minichromosomes assembled in vitro NF1 binding facilitates access of PR to the hormone-responsive elements (HREs) by precluding reforming of the histone octamer, but the function of NF1 in living cells remains unclear. Here we show that depleting NF1 by small interfering RNAs or mutating the NF1-binding site significantly compromises transcription of the MMTV promoter. The central HREs 2 and 3 are not needed for ATP-dependent H2A/H2B displacement or NF1 binding but are critical for full PR binding and MMTV transactivation. We found that NF1 binding to the MMTV promoter on a H3/H4 histone tetramer particle exposes the central HREs and facilitates their binding by PR, suggesting a possible mechanism for the reciprocal synergism between PR and NF1.